2014
DOI: 10.1177/0146167213520457
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to Control Prejudice Predicts Categorization of Multiracials

Abstract: Virginia, 1967). Since then, interracial marriage in the United States has been steadily growing-in 2010, 15% of new marriages were between persons of different races (Hayes, 2012). As such, it is not surprising that the number of multiracial individuals in the United States is increasing as well, with the most common multiracial background being Black-White multiracial (U.S. Census, 2010). In fact, multiracials are now one of the fastest growing racial groups in the country, yet social psychologists are only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 41 publications
6
56
2
Order By: Relevance
“…Consistent with work showing that prejudice increases the difficulty of categorizing faces countering race-based expectations (e.g., Blascovich et al , 1997; Hehman et al , 2014), prejudice positively correlated with category competition among prototypically low vs high Black faces. Although IMS marginally also predicted this difference in our second model (as might be expected, see Chen et al , 2014), this relationship only emerged when including ATB. This suggests a critical role of explicit prejudice in predicting category competition for prototypically varying Black faces.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Consistent with work showing that prejudice increases the difficulty of categorizing faces countering race-based expectations (e.g., Blascovich et al , 1997; Hehman et al , 2014), prejudice positively correlated with category competition among prototypically low vs high Black faces. Although IMS marginally also predicted this difference in our second model (as might be expected, see Chen et al , 2014), this relationship only emerged when including ATB. This suggests a critical role of explicit prejudice in predicting category competition for prototypically varying Black faces.…”
Section: Discussionsupporting
confidence: 73%
“…Indeed, higher IMS perceivers (who often have lower explicit prejudice; Table 1) more likely categorize racially ambiguous faces as multiracial, vs using mono-racial categorization (Chen et al , 2014). Although explicit prejudice corresponded with category competition and ACC activity in the current research, IMS, which is associated with controlling race-biased responses (Amodio et al , 2003), marginally corresponded with category competition, but not ACC activity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, individual differences that involve openness to experience and willingness to consider unconventional ideas may correlate with increased use of the Multiracial category. Chen, Moons, Gaither, Hamilton, and Sherman () found that individuals with strong egalitarian values (Plant & Devine, ) were more likely to make Multiracial categorizations of Black‐White ambiguous faces. This relationship was not explained by egalitarian individuals having increased interracial contact or lower racial prejudice.…”
Section: The Emerging “Multiracial” Categorymentioning
confidence: 99%
“…For example, conditions of economic scarcity (Rodeheffer et al , 2012; Ho et al , 2013; Krosch and Amodio, 2014), political orientation (Krosch et al , 2013), semantic labels (Tskhay and Rule, 2015) and motivation to be unbiased (Chen et al , 2014) all have been shown to affect the categorization of racially ambiguous faces.…”
Section: Introductionmentioning
confidence: 99%